Presidential Rhetoric in the COVID-19 Pandemic Era: Jokowi’s Aristotelian Rhetorical Leadership Models Before and After Implementation of Semi-Lock Down Policy - Nyarwi Ahmad (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
Presidential rhetoric evolved across the globe. Knowledge regarding the ways the presidents in democratic countries, which followed the presidential government system, such as Indonesia, advanced Aristotelian rhetorical leadership models in the covid-19 pandemic era, has, however, under-developed. Selecting president Joko Widodo (Jokowi) as a study case, this work raises the following question: what types of Aristotelian rhetorical leadership models performed by Jokowi before and after semi-lock down policy (PSBB) and how did he advance such rhetorical leaderships models? Focusing on such questions, this work adopts the president’s rhetorical leadership models, posited by Teten (2007) and Aristotelian rhetoric models, formulated by Gottweis (2007), as a conceptual framework. The materials posted in official Facebook pages of president Joko Widodo were extracted using the classic content and the qualitative and thematic content analyses. The findings are follows. Soon after the covid-19 pandemic outbreak took place in Indonesia, he attempted to develop the following types of rhetorical leadership, which are the identification, the authority and the directive rhetoric and the etho -logo-, and patho-centric Aristotelian rhetoric. Based on Indonesia case, this work offers the following knowledge contribution. It gives us new knowledge of 9 Aristotelian rhetorical leadership models, which are the etho-, logo- and patho-centric identification rhetoric, the etho-, logo- and patho-centric authority rhetoric and the etho-, logo- and patho-centric directive rhetoric models. Not merely the presidents, but also the local governments’ leaders could adopt such rhetoric models when they want to resolve diverse issues resulting from the pandemic.